Analytics for the comparison of Mughlai and Awadhi cuisine network graphs to visualize the usage of ingredients in cuisine groups - Varadaiah Manikantaa; Kumara Shambulingaiah Sringar
Indian cuisines are known for its exquisite delicacy and there are over 5000 such traditional preparations practiced in the country. Some of these cuisines are identified with cuisine families such as Mughlai, Awadhi, Udupi, Chettinad, Hyderabadi, Punjabi and so on. These cuisine groups might have emerged owing to various historical and geographical factors viz., food availability, climatic conditions, cooking traditions and cultural choices over a period. However, the divergence or convergence among the selected cuisine families other than referring to the attributes in the subjective manner, are rarely studied. This study focuses on data mining coupled with visual analytic methods for comparison of Mughlai and Awadhi cuisines